A new species related to Ypthima praenubila Leech, 1891 in Vietnam and China (Lepidoptera, Nymphalidae, Satyrinae) - Monastyrskii, Alexander L.; Lang, Song-Yun; Uémura, Yoshinobu; van Lien, Vu (Zootaxa, 2022)
We describe a new species of satyrine butterfly, Ypthima thao Monastyrskii & Lang sp. nov., recently discovered in northern Vietnam and southwestern China. This species is similar to Y. praenubila, which is distributed in the same region, and we speculate on their biogeographic origins.